(untitled) (Innovative professional education, 2025)
The speech considers the importance of using the professional achievements of the outstanding German architect and architectural theorist Ernst Neufert (1900 – 1986) in the professional education of future environmental designers. From the very beginning of his rich creative career, E. Neufert has paid much attention to the rationalization process in construction and issues of standardization. His works aimed at developing regulatory rules for industrial architecture have become the basis for the creative and design activities of many generations of environmental and architectural design specialists, contributing to the formation of professional skills and abilities, and therefore the development of project competence in general. E. Neufert’s fundamental work «Building Design» has become a kind of alphabet, a reference book for every practicing specialist in the field of environmental and architectural design